PENGARUH KUALITAS PRODUK, PROMOSI DAN LAYANAN PURNAJUAL TERHADAP CITRA MEREK HANDPHONE SAMSUNG DI 6 (ENAM) GERAI/TOKO PENJUAL HANDPHONE DI KECAMATAN UNAAHA - S. Haris, Tasman; Laena, Nur (Lafadz Jaya Publisher, 2023)
This study aims to determine the effect of product quality, promotion and after-sales service on the brand image of Samsung mobile phones in 6 (six) outlets/shops selling mobile phones in Unaaha District. The data collection method was carried out through questionnaires distributed to the public who purchased Samsung mobile phones at 6 (six) outlets/shops selling mobile phones, totaling 100 respondents. The analytical method used in this study was multiple linear regression analysis. The data obtained were then processed using SPSS version 26. The results showed that product quality, promotion and after-sales service simultaneously and partially had a positive and significant effect on the brand image of Samsung mobile phones in 6 (six) mobile phone outlets/shops in Unaaha District.